BATIK TRAINING ON NURSING HOUSE ‘WANITA UTAMA’ SURAKARTA - Riani, Asri Laksmi; Handayani, Sarah Rum; Rahmawati, Rahmawati (Muhammadiyah University Press, 2011)
The purpose of this study is to be able to guide and direct the prostitutes (WTS) in Surakarta and it?s surrounding environment on the nursing house